Scientific production related to basketball in Brazilian theses and dissertations: Bibliometric analysis Produção científica relacionada ao basquetebol em teses e dissertações brasileiras: Análise bibliométrica Producción científica relacionada al baloncesto en tesis y disertaciones brasileñas: Análisis bibliométrico - Maciel L.F.P.* (2019)
© 2019, Universidade Federal do Rio Grande do Sul. All rights reserved.This study mapped and explored scientific production related to basketball in Brazilian theses and dissertations in the 21st century. The works were selected from the Digital Library of Theses and Dissertations, the Coordination for Improvement of Higher Education Personnel’s Bank of Theses and Dissertations, and Google Scholar, through the equation Basquete* OR Basket*. The search resulted in 79 articles, including 18 theses and 61 dissertations. The State University of Campinas and Brazil’s South and Southeast stood out as the HEI and the regions with the highest number of studies respectively. In addition, the study found that aspects related to the physiological and pedagogical axes received more attention in studies, and key words basquetebol (basketball) and capacidade/habilidade (ability/skill) were prominent. The information showed how incipient works on basketball sponsored by funding agencies are in Brazil.